Emigration and development. What are the links? - Marina Murat (Global Labor Organization (GLO), 2021)
The `mobility transition' hypothesis – with emigration first increasing and then decreasing as a country develops – (Zelinsky, 1971) is often interpreted as a stylised fact, which bears the implication that immigration into rich countries will grow as low-income countries develop. This paper tests the relationships between development and emigration from 130 developing countries during 25 years. Results, robust to different semiparametric and parametric specifications, show that emigration from low to middle-income countries declines as income increases, education improves or population growth slows down. The stage of development at home also affects the main destinations of emigration. Immigration into rich economies increases from countries at intermediate levels of development. Hence, policies supporting development in low-income countries are associated with less emigration to all destinations, including that to rich economies.
Keywords: F22; J11; O11; 330; emigration; income; development; demographic transitions